Can vitamin D status influence seroconversion to SARS-COV2 vaccines? - Shahini, Endrit; Pesce, Francesco; Argentiero, Antonella; Solimando, Antonio Giovanni (Frontiers in Immunology, 2022)
Existing data indicate an association between vitamin D deficiency and increased severity of respiratory distress due to COVID-19 infection, especially in high-risk populations. To date, the effect of vitamin D on immunogenicity to SARS-CoV-2 vaccines has been investigated solely in young healthcare workers in a few studies, yielding conflicting findings, yet highlighting that the response to immunization is inversely related to age. Vitamin D status can potentially influence the antibody titers in people with a previous (or naïve) SARS-CoV-2 infection and vaccination, given its role in immune regulatory functions. From this standpoint, vitamin D supplementation can help reduce the risk of SARS-CoV-2 infection, COVID-19 severity/mortality and rebalance immunological function, particularly in subjects with vigorous T lymphocyte responses to COVID-19. However, more research is needed to establish a correlation between vitamin D status and the generation of protective serological responses to SARS-CoV-2 vaccination.